The Effects of Chinese Herbal Medicines on the Quorum Sensing-Regulated Virulence in Pseudomonas aeruginosa PAO1 - Chong, Yee Meng; How, Kah Yan; Yin, Wai Fong; Chan, Kok Gan (MDPI, 2018)
The quorum sensing (QS) system has been used by many opportunistic pathogenic bacteria to coordinate their virulence determinants in relation to cell-population density. As antibiotic-resistant bacteria are on the rise, interference with QS has been regarded as a novel way to control bacterial infections. As such, many plant-based natural products have been widely explored for their therapeutic roles. These natural products may contain anti-QS compounds that could block QS signals generation or transmission to combat QS pathogens. In this study, we report the anti-QS activities of four different Chinese herbal plant extracts: Poria cum Radix pini, Angelica dahurica, Rhizoma cibotii and Schizonepeta tenuifolia, on Pseudomonas aeruginosa PAO1. All the plants extracted using hexane, chloroform and methanol were tested and found to impair swarming motility and pyocyanin production in P. aeruginosa PAO1, particularly by Poria cum Radix pini. In addition, all the plant extracts also inhibited violacein production in C. violaceum CV026 up to 50% while bioluminescence activities were reduced in lux-based E. coli biosensors, pSB401 and pSB1075, up to about 57%. These anti-QS properties of the four medicinal plants are the first documentation that demonstrates a potential approach to attenuate pathogens’ virulence determinants.